Immunohistochemical, tomographic and histological study on onlay iliac grafts remodeling - Faria, Paulo E. P.; Okamoto, Roberta [UNESP]; Bonilha-Neto, Ricardo M.; Xavier, Samuel P.; Santos, Antonio C.; Salata, Luiz A. (Wiley, 2008)
The information concerning the molecular events taking place in onlay bone grafts are still incipient. The objective of the present study is to correlate the effects of perforation of resident bone bed on (1) the timing of onlay autogenous graft revascularization; (2) the maintenance of volume/density of the graft (assessed through tomography); and (3) the occurrence of bone remodeling proteins (using immunohistochemistry technique) delivered in the graft. Thirty-six New Zealand White rabbits were subjected to iliac crest onlay bone grafting on both sides of the mandible. The bone bed was drill-perforated on one side aiming at accelerating revascularization, whereas on the other side it was kept intact. After grafts fixation and flaps suture all animals were submitted to tomography on both mandible sites. Six animals were sacrificed, respectively, at 3, 5, 7, 10, 20 and 60 days after surgery. A second tomography was taken just before sacrifice. Histological slides were prepared from each grafted site for both immunohistochemistry analysis [osteopontin, osteocalcin, type I collagen and vascular endothelial growth factor (VEGF) anti-bodies] and histometric analysis. The values on bone volume measured on tomography showed no statistic significance (P≥0.05) between perforated and intact sites. Grafts placed on perforated beds showed higher bone density values compared with non-perforated ones at 3 days (P≤0.05). This correlation was inverted at 60 days postoperatively. The findings from VEGF labeling revealed a tendency for earlier revascularization in the perforated group. The early revascularization of bone grafts accelerated the bone remodeling process (osteocalcin, type I collagen and osteopontin) that led to an increased bone deposition at 10 days. The extended osteoblast differentiation process at intermediate stages in the perforated group cooperated for a denser bone at 60 days. © 2008 Blackwell Munksgaard.
Keywords: Autogenous bone graft; Computed tomography; Immunohistochemical; Revascularization; collagen type 1; osteocalcin; osteopontin; vasculotropin A; angiogenesis; animal; bone density; bone remodeling; bone transplantation; iliac bone; immunohistochemistry; jaw; mandible; physiology; rabbit; tomography; vascularization; Alveolar Process; Animals; Bone Density; Bone Remodeling; Bone Transplantation; Collagen Type I; Ilium; Immunohistochemistry; Mandible; Neovascularization, Physiologic; Osteocalcin; Osteopontin; Rabbits; Tomography, X-Ray; Vascular Endothelial Growth Factor A